Micro-structure and motion of two-dimensional dense short spherocylinder liquids. (28th February 2018) - Wang, Wen; Lin, Jyun-Ting; Su, Yen-Shuo; I, Lin
Abstract: We numerically investigate the micro-structure and motion of 2D liquids composed of dense short spherocylinders, by reducing the shape aspect ratio from 3. It is found that reducing shape aspect ratio from 3 causes a smooth transition from heterogeneous structures composed of crystalline ordered domains with good tetratic alignment order to those with good hexagonal bond-orientational order at an aspect ratio equaling 1.35. In the intermediate regime, both structural orders are strongly deteriorated, and the translational hopping rate reaches a maximum due to the poor particle interlocking of the disordered structure. Shortening rod length allows easier rotation, induces monotonic increase of rotational hopping rates, and resumes the separation of rotational and translational hopping time scales at the small aspect ratio end, after the crossover of their rates in the intermediate regime. At the large shape aspect ratio end, the poor local tetratic order has the same positive effects on facilitating local rotational and translational hopping. In contrast, at the small shape aspect ratio end, the poor local bond orientational order has the opposite effects on facilitating local rotational and translational hopping.